Is anybody there? : a novel - Bunting, Eve, 1928- (New York : Lippincott, 1988)
After discovering the disappearance of several household items, Marcus, a thirteen-year-old latchkey child, suspects that a stranger may be prowling around inside his house while he's at school and his mother is at work.
Booklist.
School Library Journal.
Wilson's Junior High School.
5.9
4-6
5-8
Keywords: Latchkey children -- Fiction; Mothers and sons -- Fiction; Latchkey children -- Fiction; Mothers and sons -- Fiction